Аналіз методів біометричної ідентифікації - Копиця, А. А. (ХНУРЕ, 2024)
This work is devoted to the analysis of biometric identification methods. Biometrics is a type of information technology that is rapidly developing during the XXI century and determines the development of means of verification and identification systems for individuals. This technology is used in management and control systems to ensure security. The main advantage of biometrics is the ability to quickly and easily identify a person without causing inconvenience to the person. Today, biometrics is a science that uses unique human measurement parameters for verification. It includes access systems based on fingerprints and palm prints, iris, facial geometry, vein patterns, DNA, signature and voice, etc.
Keywords: біометрична ідентифікація; biometric identification